Inequities in the delivery of mental health care: a grounded theory study of the policy context of primary care - Ashcroft, Rachelle; Menear, Matthew; Silveira, Jose; Dahrouge, Simone; Emode, Monica; Booton, Jocelyn; McKenzie, Kwame (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Strengthening capacity for mental health in primary care improves health outcomes by providing timely access to coordinated and integrated mental health care. The successful integration of mental health in primary care is highly dependent on the foundation of the surrounding policy context. In Ontario, Canada, policy reforms in the early 2000’s led to the implementation of a new interprofessional team-model of primary care called Family Health Teams. It is unclear the extent to which the policy context in Ontario influenced the integration of mental health care in Family Health Teams emerging from this period of policy reform. The research question guiding this study was: what were key features of Ontario’s policy context that influenced FHTs capacity to provide mental health services for mood and anxiety disorders? Methods A qualitative study informed by constructivist grounded theory. Individual interviews were conducted with executive directors, family physicians, nurse practitioners, nurses, and the range of professionals who provide mental health services in interprofessional primary care teams; community mental health providers; and provincial policy and decision makers. We used an inductive approach to data analysis. The electronic data management programme NVivo11 helped organise the data analysis process. Results We conducted 96 interviews with 82 participants. With respect to the contextual factors considered to be important features of Ontario’s policy context that influenced primary care teams’ capacity to provide mental health services, we identified four key themes: i) lack of strategic direction for mental health, ii) inadequate resourcing for mental health care, iii) rivalry and envy, and, iv) variations across primary care models. Conclusions As the first point of contact for individuals experiencing mental health difficulties, primary care plays an important role in addressing population mental health care needs. In Ontario, the successful integration of mental health in primary care has been hindered by the lack of strategic direction, and inconsistent resourcing for mental health care. Achieving health equity may be stunted by the structural variations for mental health care across Family Health Teams and across primary care models in Ontario.